2017
DOI: 10.1111/nhs.12386
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of unprofessional behaviors in the emergency department: A qualitative study

Abstract: The nursing profession is focused on serving others and has high expectations that each member behaves professionally and ethically, as articulated in nursing codes of practice and conduct. Where these are not upheld, inappropriate and unprofessional workplace behaviors follow. Regrettably, unprofessional behavior is neither new nor constrained to the nursing profession, but is known to negatively impact staff and workplace relationships, and importantly, patient safety and care. The aim of this qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…High-quality emergency team collaboration can strengthen confidence in the team, help to decrease the incidence of errors, improve treatment outcomes in patients, and demonstrate efficacy in emergency resuscitation, which increases patient consultation and nursing staff job satisfaction [6]. Job satisfaction in emergency department staff does not arise only from salaries; affirmation and recognition from supervisors and peers is a more important source of job satisfaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality emergency team collaboration can strengthen confidence in the team, help to decrease the incidence of errors, improve treatment outcomes in patients, and demonstrate efficacy in emergency resuscitation, which increases patient consultation and nursing staff job satisfaction [6]. Job satisfaction in emergency department staff does not arise only from salaries; affirmation and recognition from supervisors and peers is a more important source of job satisfaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the participants of a study indicated the importance of team work in providing care for patients, effective cooperation with each other, and their role in occupational and moral satisfaction. They also stated that team work is effective on the relationship between the team members (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, witnessing clinical nurses enacting unprofessional behaviors, such as reluctance to disclose safety issues (e.g. Parizad et al, ), might also have prevented the likelihood of students reporting safety issues that occurred during the practice. All these aspects suggest that a periodical reflection on what constitutes a PS incident, and how and when to report it (Espin & Meikle, ; Fagan et al, ) should be included in nursing degree programs.…”
Section: Discussionmentioning
confidence: 99%